2009
DOI: 10.13057/biodiv/d110103
|View full text |Cite
|
Sign up to set email alerts
|

Systematic studies of Australian stipoid grasses (Austrostipa) based on micro-morphological and molecular characteristics

Abstract: Bustam BM (2010) Systematic studies of Australian stipoid grasses (Austrostipa) based on micro morphological and molecular characteristics. Biodiversitas 11: 9-14. This research is one of many studies on stipoid grasses organized by the International Stipeae Working Group (ISWG). This research tested the subgeneric classification of Austrostipa proposed by Jacobs and Everett (1996) and tested how informative the micro morphological characters used. Data were collected from herbarium specimens of 36 species (33… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…It is rather a contribution to obtain monophyletic taxa, which can serve as reliable units addressing questions about character evolution and/or biogeography in Austrostipa, which have been barely touched upon to date. Some of our suggestions for classification are not new, having been made in previous molecular phylogenetic studies of Austrostipa, for example, the maintenance of subgenera Falcatae (Jacobs et al, 2007;Bustam, 2010Bustam, , 2012Syme et al, 2012), Longiaristatae and Lobatae (Jacobs et al, 2007;Syme et al, 2012), the broadening of subg. Austrostipa to include also subgenera Tuberculatae (Jacobs et al, 2007;Syme et al, 2012) and Eremophilae (Syme et al, 2012), but our data do not support combining subgenera Arbuscula and Bambusina, a suggestion based on their similar habit (Jacobs et al, 2007).…”
Section: Delineation and Relationship Of Subgeneramentioning
confidence: 98%
See 1 more Smart Citation
“…It is rather a contribution to obtain monophyletic taxa, which can serve as reliable units addressing questions about character evolution and/or biogeography in Austrostipa, which have been barely touched upon to date. Some of our suggestions for classification are not new, having been made in previous molecular phylogenetic studies of Austrostipa, for example, the maintenance of subgenera Falcatae (Jacobs et al, 2007;Bustam, 2010Bustam, , 2012Syme et al, 2012), Longiaristatae and Lobatae (Jacobs et al, 2007;Syme et al, 2012), the broadening of subg. Austrostipa to include also subgenera Tuberculatae (Jacobs et al, 2007;Syme et al, 2012) and Eremophilae (Syme et al, 2012), but our data do not support combining subgenera Arbuscula and Bambusina, a suggestion based on their similar habit (Jacobs et al, 2007).…”
Section: Delineation and Relationship Of Subgeneramentioning
confidence: 98%
“…More recently, Romaschenko et al (2010Romaschenko et al ( , 2012 have described two major lemma epidermal patterns in the tribe: Stipa-like, also called saw-like, dominated by long fundamental cells and hooks, and Achnatherum-like, also called maize-like, dominated by short fundamental cells and paired with silica cells. Several authors have shown out that, even though LEP is relatively uniform within a genus, it may still be useful in identifying particular species as well as in delineating relationships among and between different subgenera or sections (Ortúñez and de la Fuente, 2010;Nobis, 2013;Olonova et al, 2016;Nobis et al, 2019b), but lemmas of relatively few Austrostipa species had been studied prior to Bustam's (2010;2012) work.…”
Section: Introductionmentioning
confidence: 99%
“…175. Austrostipa S. W. L. Jacobs & J. Everett Austrostipa S. W. L.Jacobs & J. Everett, Telopea 6: 582 (1996); tax., micromorphology:Bustam (2010).…”
mentioning
confidence: 99%
“…Thus, the efficiency of falcate awns in dispersing was significantly less than that of geniculate awns. Phylogenetic analyses have shown that these falcate-awned species fall into a distinct Austrostipa subgenus Falcatae (Bustam, 2010;Syme et al, 2012;Winterfeld et al, 2015), and may have evolved separate strategies for dispersal. We also found that awn length was positively correlated with overall burial depth, consistent with Garnier and Dajoz (2001) and Johnson and Baruch (2014).…”
Section: Discussionmentioning
confidence: 99%